The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1001/jamaoncol.2023.1363
|View full text |Cite
|
Sign up to set email alerts
|

Camrelizumab Plus Apatinib and Temozolomide as First-Line Treatment in Patients With Advanced Acral Melanoma

Abstract: ImportanceAcral melanoma, known for low tumor mutation burden, responds poorly to immunotherapy. A standard therapy is still lacking.ObjectiveTo investigate the activity and safety of camrelizumab (an anti–programmed cell death-1 antibody) plus apatinib (a vascular endothelial growth factor receptor 2 inhibitor) and temozolomide as first-line treatment in patients with advanced acral melanoma.Design, Setting, and ParticipantsIn this single-arm, single-center, phase 2 nonrandomized clinical trial, patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…studied combination therapy with camrelizumab, apatinib, and temozolomide as first-line therapy for 50 patients with ALM. This study found a particularly high ORR of 64%, median PFS of 18.4 months, DCR of 88%, median time to response of 2.7 months, and median duration of response of 17.5 months ( 58 ). A similar recent prospective phase II study by Wang et al., also out of China, studied 30 patients with ALM treated with first-line combination therapy with apatinib and camrelizumab.…”
Section: Managementmentioning
confidence: 62%
See 2 more Smart Citations
“…studied combination therapy with camrelizumab, apatinib, and temozolomide as first-line therapy for 50 patients with ALM. This study found a particularly high ORR of 64%, median PFS of 18.4 months, DCR of 88%, median time to response of 2.7 months, and median duration of response of 17.5 months ( 58 ). A similar recent prospective phase II study by Wang et al., also out of China, studied 30 patients with ALM treated with first-line combination therapy with apatinib and camrelizumab.…”
Section: Managementmentioning
confidence: 62%
“…Other combinations including medications such as camrelizumab, apatinib, and temozolomide have also shown promising results ( 58 , 59 ). A prospective study treating patients with a combination of camrelizumab, apatinib, and temozolomide found a particularly high ORR of 64% and DCR of 88% ( 58 ). A similar DCR was found in a study using a regimen of apatinib and camrelizumab, but the ORR was found to be lower, at 24.1% ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation